Potency of Mangrove Leaves (Rhizophora mucronata) Containing Bioactive Compounds as Source of Antioxidant: A Review - Rahmawati; Yushinta Aristina Sanjaya; Yunita Satya Pratiwi; Elistiya Putri Nuraini Hendrawan; Zhafa Nesya Salsabila; Tania Amalia (International Journal of Eco-Innovation in Science and Engineering (IJEISE), 2023)
Bioactive compounds derived from plants are gaining attention worldwide because they have beneficial effects on humans. Rhizophora mucronata is a species of mangrove plant that has slightly dark leaves and glossy green on the top of the leaves and pale green on the bottom and acts as a natural antioxidant which has traditionally been used as a food ingredient and traditional medicine. Therefore, this article was written to review the bioactive compounds in Rhizophora mucronata leaves, antioxidant levels and the benefits of antioxidants in food and health products. This article summarizes relevant literature regarding R. mucronata which was tested using Phytochemical screening, FTIR and DPPH (1,1-diphenyl-2-picrylhydrazyl) methods. Phytochemical analysis revealed the presence of alkaloids, flavonoids, steroids, phenolics, tannins and saponins. Based on the FTIR test, R. mucronata leaf extract showed the presence of –OH, C-H (aromatic), C=C (aromatic), and C-O groups. The antioxidant capacity expressed in IC50 (mg/mL) shows that R. mucronata has the potential to be used as a source of natural antioxidants. Antioxidants can play a role in improving the sensory quality of a food product and as a natural bactericidal so that it can be used to maintain aquatic biota and food preservatives. In addition, antioxidants contained in mangroves can prevent aging, wrinkles, cancer, obesity, and diabetes mellitus.